Evaluation of Deposition and Clearance of Asbestos (Detected by SEM-EDS) in Lungs of Deceased Subjects Environmentally and/or Occupationally Exposed in Broni (Pavia, Northern Italy) - Visonà, Silvia D.; Capella, Silvana; Bodini, Sofia; Borrelli, Paola; Villani, Simona; Crespi, Eleonora; Colosio, Claudio; Previderè, Carlo; Belluso, Elena (Frontiers in Public Health, 2021)
Biodurability is one of the main determinants of asbestos hazardousness for human health. Very little is known about the actual persistence of asbestos in lungs and its clearance, nor about differences in this regard between the different mineralogical types of asbestos. The aim of the present study was to evaluate the amount, the dimensional characteristics and the mineralogic kinds of asbestos in lungs (measured using SEM-EDS) of a series of deceased subjects who were certainly exposed to asbestos (mainly crocidolite and chrysotile) during their life. Moreover, we investigated possible correlations between the lung burden of asbestos (in general and considering each asbestos type), as well as their dimension (length, width and l/w ratio) and the duration of exposure, the latency- in case of malignant mesothelioma (MM), the survival and the time since the end of exposure. In 62.5% of subjects, asbestos burden in lungs was lower that the threshold considered demonstrative for occupational exposure. In 29.1% of cases no asbestos was found. Chrysotile was practically not detected. The mean length of asbestos fibers and the length to width ratio were significantly related to the duration of exposure to asbestos. No other statistically significant correlations were found between the amount and dimensional characteristics of asbestos (nor with the relative amount of each asbestos type) and the other chronological variables considered. In conclusion, it was pointed out that chrysotile can be completely removed from human lungs after less than 8 years and, instead, amphiboles persist much more time. The present results suggest, as well, that the finding of no asbestos in lungs cannot rule out the attribution of MM to asbestos (in particular, chrysotile) inhaled in an occupational setting. This point is of crucial importance from a legal point of view.